Compactação de solos cultivados com amendoim: efeitos do tráfego e de sistemas de manejo - RODRIGUES, Gustavo Sanches; SILVA, Fagner Luiz Rodrigues; FLORA, Murillo Pereira; GUIMARÃES JUNNYOR, Wellingthon da Silva; SANTOS, Maria Aparecida do Nascimento; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2023)
-